Using the substitution u = ln(x), find the general solution of the differential equation y = x^2*(d^2(y)/dx^2) + x(dy/dx) + y = 0

dy/dx = (dy/du)(1/x), d^2(y)/dx^2 = (d^2(y)/du^2)(1/(x^2)) - (dy/du)*(1/(x^2))   

(x^2)( (d^2(y)/du^2)(1/(x^2)) - (dy/du)(1/(x^2)) ) + x(dy/du)*(1/x) + y = 0       

d^2(y)/du^2 - dy/du + dy/du + y = 0  

d^2(y)/du^2 + y = 0

y = Asin(u) + Bcos(u)

y = Asin(ln(x)) + Bcos(ln(x))                   

Related Further Mathematics A Level answers

All answers ▸

How to integrate ln(x)?


It is given that f(x)=(x^2 +9x)/((x-1)(x^2 +9)). (i) Express f(x) in partial fractions. (ii) Hence find the integral of f(x) with respect to x.


Express (X²-16)/(X-1)(X+3) in partial fractions


Why is the argument of a+bi equal to arctan(b/a)?


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences